Pemikiran Ilmuwan Ekonomi Klasik (Zaid Bin Ali, Abu Hanifah, Abu Yusuf, Abu Ubaid) - Khulaelatudil Azzah; Lutfiyanti; Elda Purwanti; Muhammad Taufiq Abadi; Muhammad Aris Syafi’i (JURNAL ILMIAH RESEARCH STUDENT, 2024)
The aim of this research is to examine the economic thoughts of classical Muslim scientists, some of which may still be relevant today. History is a field of science that is free to be interpreted by researchers. Therefore, it is not uncommon to find several historical articles that do not seem to fully describe historical events that occurred in the field. One of the things that must be considered is the progress achieved by Islamic civilization through the mastery of science, which currently seems unclear. The results of this research show that the ideas of classical scientists are still relevant today. For example, when Zaid Bin Ali sold goods on credit at a higher price than cash, he enabled the sale of the goods. However, Zayd bin Ali does not allow the price of deferred payments to be higher than cash payments, such as additional payments when postponing loan payments. Honey zakat, salam contract, and hawalah contract are some, according to Abu Hanifah's opinion. The thoughts of Abu Yusuf and Abu Ubaid are still used in various forms according to the times.